The role of ligands on protein retention in adsorption chromatography: A surface energetics approach. Issue 6 (16th February 2014) - Aasim, Muhammad; Kakarla, Prasad Babu; D'Souza, Roy N.; Bibi, Noor Shad; Klein, Tanja Yvonne; Treccani, Laura; Rezwan, Kurosch; Fernández‐Lahore, Marcelo
<x xml:space="preserve">Abstract</x> Protein adsorption onto hydrophobic chromatographic supports has been investigated using a colloid theory surface energetics approach. The surface properties of commercially available chromatographic beads, Toyopearl Phenyl 650‐C, and Toyopearl Butyl 650‐C, have been experimentally determined by contact angle and zeta potential measurements. The adsorption characteristics of these beads, which bear the same backbone matrix but harbor different ligands, have been studied toward selected model proteins, in the hydrated as well as dehydrated state. There were two prominent groups of proteins observed with respect to the chromatographic supports presented in this work: loosely retained proteins, which were expected to have lower average interaction energies, and the strongly retained proteins, which were expected to have higher average interaction energies. Results were also compared and contrasted with calculations derived from adsorbent surface energies determined by inverse liquid chromatography. These results showed a good qualitative agreement, and the interaction energy minima obtained from these extended Derjaguin, Landau, Verwey and Overbeek calculations were shown to correlate well with the experimentally determined adsorption behavior of each protein.